CEO Power and Stock Price: An Emperical Study of Indonesia Automotive and Components Listing Firms - Gusni, (International Journal of Psychosocial Rehabilitation, 2020)
The relationship between CEO power and stock price is still an interesting issue in the literature of corporate finance. The purpose of this study is to identify the effect of CEO power on the firm's stock pricing. The study is also interested in showing factors that investors rely on to make their investment decisions in the automotive and component firms listed in the Indonesian capital market. This research uses secondary data gathered from the official website of Indonesia Capital Market. In order to fulfill the research objective, this study used a panel data analysis method in which the sample was taken from 12 firms by using a purposive sampling technique. The research finding was that CEO power has a strong effect on the firm's stock price. Our finding is important for the investor as information and consideration in making investment decisions.